O-Convexity of Orlicz-Bochner Spaces with Orlicz Norm (Communications in Mathematical Research, 2019)
In this paper we give some characterizations of O-convexity of Banachspaces, and show the criteria for O-convexity in Orlicz-Bochner function space $L_M(μ,\,X)$ and Orlicz-Bochner sequence space $l_M(X_s)$ endowed with Orlicz norm.Moreover, we give a sufficient condition for the dual of such a space to have the fixedpoint property.